2021
DOI: 10.1186/s12884-021-03911-5
|View full text |Cite
|
Sign up to set email alerts
|

Resilience mediates the effect of self-efficacy on symptoms of prenatal anxiety among pregnant women: a nationwide smartphone cross-sectional study in China

Abstract: Background Prenatal anxiety is one of the most prevalent mental disorders during pregnancy. This study assessed the prevalence of prenatal anxiety and examined whether resilience could play the mediating role in the association between self-efficacy and symptoms of prenatal anxiety among pregnant women in China. Methods A nationwide smartphone cross-sectional study was carried out in three cities (Shenyang of Liaoning Province, Zhengzhou of Henan P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 56 publications
2
25
0
5
Order By: Relevance
“…The RS-14 scoring ≤ 63, between 64 and 73, and ≥ 74 indicate being lowly, moderately, and highly resilient, respectively (13). The Chinese version of the RS-14 had strong reliability and validity (47,48). In this study, Cronbach's α coefficient of the scale was 0.967.…”
Section: Measurement Of Resiliencementioning
confidence: 54%
“…The RS-14 scoring ≤ 63, between 64 and 73, and ≥ 74 indicate being lowly, moderately, and highly resilient, respectively (13). The Chinese version of the RS-14 had strong reliability and validity (47,48). In this study, Cronbach's α coefficient of the scale was 0.967.…”
Section: Measurement Of Resiliencementioning
confidence: 54%
“…In addition, self-efficacy plays a significant role in fostering resilience ( Kumfer, 1999 ; Cody, 2013 ; Rees et al, 2015 ), which has been confirmed as the strongest predictor of professional identity ( Bhattarai et al, 2020 ; Zhang et al, 2021 ). However, no empirical study has examined the mediating role of resilience in the relationship between self-efficacy and professional identity ( Hayat et al, 2021 ; Ma et al, 2021 ). Lastly, role models play an important role in the development of professional identity in FNS ( Paice, 2002 ; Sternszus et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the significant stigmatization of mental health in Asian culture [ 17 ], many Chinese women with antenatal depression do not seek help, and thus under-recognition and under-treatment of antenatal depression among Chinese women is common [ 18 ]. To address this problem, a shift from traditional views that emphasize weakness, illness, and pathology towards a positive psychology perspective could provide a promising approach to preventing antenatal depression [ 19 ]. Unlike traditional views, positive psychology (eg.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies and the following assumptions, we proposed that PsyCap functions as an important mediator. Women with higher self-efficacy may have more confidence to cope with risk during the pregnancy [ 29 ]; hope may contribute to a woman’s positive expectancy toward the fetus and their own health and have less focus on negative effects related to older age [ 30 ]; women with optimistic views may have positive attributions to pregnancy outcomes and deflect responsibility for negative events through an optimistic explanation [ 31 ]; when facing stressors during pregnancy, women with resilience may bounce back to normal life more quickly [ 19 , 32 ].…”
Section: Introductionmentioning
confidence: 99%